2022
DOI: 10.3390/s22134995
|View full text |Cite
|
Sign up to set email alerts
|

Beam Wander Restrained by Nonlinearity of Femtosecond Laser Filament in Air

Abstract: The filamentation process under atmospheric turbulence is critical to its remote-sensing application. The effects of turbulence intensity and location on the spatial distribution of femtosecond laser filaments in the air were studied. The experimental results show that the nonlinear effect of the filament can restrain the beam wander. When the turbulence intensity was 3.31×10−13 cm−2/3, the mean deviation of the wander of the filament center was only 27% of that of the linear transmitted beam. The change in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Femtosecond laser filaments are inevitably affected by atmospheric turbulence in air, which poses an unavoidable problem for the practical application of femtosecond laser filaments. Recently, some studies have been reported on the effect of atmospheric turbulence on femtosecond laser filament formation [13,14] . Turbulence induces the fluctuation of the surrounding air density, consequently causing refractive index variations and distorting optical waves, which leads to a transverse stochastic distribution, increased filament counts, and expanded spot size [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond laser filaments are inevitably affected by atmospheric turbulence in air, which poses an unavoidable problem for the practical application of femtosecond laser filaments. Recently, some studies have been reported on the effect of atmospheric turbulence on femtosecond laser filament formation [13,14] . Turbulence induces the fluctuation of the surrounding air density, consequently causing refractive index variations and distorting optical waves, which leads to a transverse stochastic distribution, increased filament counts, and expanded spot size [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%